A Survey on Ectoparasite Infestations in Companion Dogs of Ahvaz District, South-west of Iran - B Mosallanejad; AR Alborzi; N Katvandi (Tehran University of Medical Sciences, 2012)
Background: The objective was to determine the prevalence of ectoparasite infestations in referred companion dogs to veterinary hospital of Shahid Chamran University of Ahvaz, from 2009 to 2010. Methods:A total of 126 dogs were sampled for ectoparasites and examined by parasitological methods. The studied animals were grouped based on the age (<1 year, 1-3 years and >3 years), sex, breed and region. Results: Thirty six out of 126 referred dogs (28.57%) were positive for external ectoparasites. The most common ectoparasites were Heterodoxus spinigera, which were recorded on 11 dogs (8.73%). Rhipicephalus sanguineus, Sarcoptes scabiei, Otodectes cynotis, Xenopsylla cheopis, Cetenocephalides canis, Cetenocephalides felis, Hippobosca sp. and myiasis (L3 of Lucilia sp.) were identified on 9 (7.14%), 7 (5.56%), 6 (4.76%), 3 (2.38%), 3 (2.38%), 2 (1.59%), 2 (1.59%) and one (0.79%) of the studied dogs respectively. Mixed infestation with two species of ectoparasites was recorded on 8 (6.35%). Prevalence was higher in male dogs (35.82%; 24 out of 67) than females (20.34%; 12 out of 59), age above 3 years (31.81%; 7 out of 22) and in the season of winter (30.95%; 13 out of 42), but the difference was not significant regarding to host gender, age and season (P>0.05). Conclusion:Apparently this is the first study conducted in companion dogs of Ahvaz District, South-west of Iran. Our results indicated that lice and ticks were the most common ectoparasites in dogs of this area. The zoonotic nature of some ectoparasites can be regard as a public health alert.